KARAKTERISTIK TOKO PEMPEK BERDASARKAN FASILITAS DI KOTA PALEMBANG - Gemala Cahya; Selly Ratna Sari; Lifianthi; Elisa Wildayana (Clarias : Jurnal Perikanan Air Tawar, 2021)
This research aims to identify the characteristics of pempek stores based on facilities. The research was conducted in six different stores by grade. Grades include Grade I until IV. Pempek stores are made based on the grade of facilities. Facilities include place, atmosphere and comfort. Grade I has open room, facilities and infrastructure. Grade II has open space room, adequate infrastructure facilities. Grade III has open and closed room, more complete facilities and infrastructure. Grade V has a closed space and facilities are quite complete while grade VI has the most complete closed room, facilities and infrastructure compared to other grades. So that grade VI has the most complete character.